2016
DOI: 10.1245/s10434-016-5630-4
|View full text |Cite
|
Sign up to set email alerts
|

Shape and Enhancement Characteristics of Pancreatic Neuroendocrine Tumor on Preoperative Contrast-enhanced Computed Tomography May be Prognostic Indicators

Abstract: Irregular tumor shape/enhancement on preoperative computed tomography is a negative prognostic factor after curative surgery for PNET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Cheng et al [18] found a strong correlation between the peri-spheroid solid stress distribution and spheroid shape, a result of the suppression of cell proliferation and induction of apoptotic cell death in regions of high mechanical stress. In addition, Mazurowski et al [19] reported that shape features were strongly associated with genomic subtypes and patient outcomes in lower-grade glioma, and Okabe et al [8] reported that irregular tumor shape on preoperative computed tomography was a negative prognostic factor after curative surgery for pancreatic neuroendocrine tumors. Therefore, we believe that there is a significant correlation between the shape of GIST and risk level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al [18] found a strong correlation between the peri-spheroid solid stress distribution and spheroid shape, a result of the suppression of cell proliferation and induction of apoptotic cell death in regions of high mechanical stress. In addition, Mazurowski et al [19] reported that shape features were strongly associated with genomic subtypes and patient outcomes in lower-grade glioma, and Okabe et al [8] reported that irregular tumor shape on preoperative computed tomography was a negative prognostic factor after curative surgery for pancreatic neuroendocrine tumors. Therefore, we believe that there is a significant correlation between the shape of GIST and risk level.…”
Section: Discussionmentioning
confidence: 99%
“…CT features like location, contour, necrosis, enhancement pattern, and tumor calcification are associated with grades [4][5][6]; few studies report how tumor shape can be correlated with risk grading. In glioblastoma [7] or pancreatic neuroendocrine tumors [8], tumor shape is associated with the outcome. Therefore, we explored a novel method for quantifying the shape of GISTs using CT.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there is emerging evidence that the radiographic characteristics of pancreatic NET on CT correlate with clinical outcomes. 19 Extrapolating from the findings of the current study, it is possible that the echogenic appearance of NELM on transabdominal US may also be prognostic. If validated in future studies, transabdominal US could be added to the pre-operative assessment in order to help ascertain the risk of recurrence of patients with NELM.…”
Section: Discussionmentioning
confidence: 54%
“…In the 2017, Zhu et al reported a significant association between the aspect of lesion borders (well-defined or ill-defined) on EUS and the grading of pNET [25]. Moreover, the association between irregular shape on CT scan and aggressiveness has been previously reported also in two large retrospective surgical series of pNET [26,27]. In our study, this feature was significant in the multivariate analysis in both pNETs and the other-than-pNET group, which indicates that this finding could reflect the infiltrative behavior of the nodule independently of its nature.…”
Section: Discussionmentioning
confidence: 86%